Evaluation of Chronic Cough in Children: A Prospective Study in a Tertiary Care Hospital (Northern International Medical College Journal, 2018)
Background : Chronic cough is a common complaint in children which causes distress, and affects the quality of life of parents and children. While cough may be seen as a common condition of childhood without serious consequences, ignoring a cough that may be the sole presenting symptom of an underlying illness can lead to delayed diagnosis and progression to a chronic respiratory morbidity.Objective : To evaluate the specific diagnosis and prognosis of chronic cough in children.Methods : A prospective study was done on children with chronic cough (history of cough>8 weeks) referred to Dhaka Shishu (Children) Hospital, a tertiary hospital.Children aged 2 to 8 years with chronic cough referred by the general physicians, pediatricians and other peripheral hospitals were the study subjects. Exclusion criteria were children with immune-deficiency,congenital anomalies of lung,congenital heart disease, gastro-intestinal disorders (e.g. gastro-esophageal reflux, peptic ulcer disease), in born error of metabolism (e.g. cystic fibrosis) and other chronic conditions (e.g. gross neurodevelopmental delay). The evaluation of chronic cough was based on simple principles: careful history-taking concerning the characteristics of the cough, full clinical examination to look for any associated symptoms and relevant investigations done. Underlying diagnoses and outcomes were ascertained after follow-up for a period of six months and treatment was given as per the management protocol of the hospital.Results : The most common final diagnosis was allergic rhinitis (31%), followed by asthma (28.6%), rhinitis coexisting with asthma (23.8%), post viral cough (16.6). Cough resolved in 54.8%, partially improved in 40.5% and persisted in 4.7% of patients.Conclusion : Allergic rhinitis with or without co-existing asthma was the commonest cause of chronic cough in children referred to this hospital.Northern International Medical College Journal Vol.9(1) July 2017: 264-266